Gray Scale and Power Doppler Sonography in Cases of Kimura Disease - Ahuja, Anil; Ying, Michael; Mok, J.S.W.; Anil, Constantine Metreweli (American Journal of Neuroradiology, 2001)
Summary: Kimura disease is a rare chronic inflammatory disorder mimicking malignancy. Nodes are present in the submental and submandibular regions, within the parotid gland, and in the upper cervical chain. On gray scale sonograms, they are hypoechoic and round, with normal hilar architecture and homogeneous internal echoes. On power Doppler sonograms, the nodes show prominent intranodal vessels with a hilar pattern and low intranodal resistance. The soft tissue and parotid lesions also show low-resistance vascularity within.